To expand or not to expand: A strategic analysis of the recycler's waste treatment capacity. (April 2019) - Liu, Jing; Nie, Jiajia; Yuan, Hongping
Highlights: The recycler does not always choose to expand its waste treatment capacity. The recycler may prefer a constant construction waste treatment fee. A recycling capacity-glut strategy can be always optimal for the recycler. A win-win situation can be achieved between the recycler and the government. Abstract: This study aims to investigate the recycler's profits and associated environmental impacts of construction and demolition waste (CDW) recycling under two waste treatment capacity expansion strategies, which primarily consider the mismatch between demand and supply in CDW recycling market. Through developing and comparing non-linear programming models in two waste recycling market scenarios, we find that in both scenarios, no matter how much the initial waste treatment capacity, a waste recycling capacity-glut strategy can be always optimal from the recycler's perspective. However, the recycler may not expand its waste treatment capacity when the initial waste treatment capacity is medium or high. Instead of decreasing its waste treatment fee, the recycler would set a constant waste treatment fee for profit attainment when the initial waste treatment capacity is high. Furthermore, although the government and the recycler commonly have conflicting objectives in CDW recycling, a win-win situation where both the recycler and the government prefer the same strategy can be achieved when the initial waste treatment capacity is low or moderate. This study not only offers new insights into understanding the recyclers' capacity expansion strategies, but also provides valuable implications for related policy development.